Management of the System of Special Physical Training of Students in Table Tennis - Xolmatov Bekzod Uralovich (Web of Journals Publishing, 2023)
This article describes the role of auxiliary physical exercises in the development of physical fitness of young table tennis players, their use and the tasks that need to be solved with these exercises, as well as information and practical recommendations on the importance of loads given to the body.
Keywords: physical fitness, general and special physical fitness, physical qualities, auxiliary exercises, strength, agility, agility, endurance, flexibility.